Religiusitas dan Komitmen Organisasi Pada Pembimbing Kemasyarakatan Balai Pemasyarakatan (BAPAS) Kelas 1 Banjarmasin - Nazmi Nazmi; Aziza Fitriah; Adila Nurlaila (Faculty of Ushuluddin and Humanities, 2023)
Community advisors are human resources (HR) within the Correctional Center organization. The problem that the researchers took was the social advisor, who did not carry out his duties and functions by the applicable institutional laws and regulations. This study aims to determine the influence of religiosity on the organization's commitment to the community guidance of Bapas Class I Banjarmasin. This research method uses a quantitative approach with simple linear regression analysis. Sampling in this study used non-probability sampling techniques with the total sample method. The subject of this study is the community supervisor of Bapas Class I Banjarmasin, with as many as 32 subjects. The scale used in this study is the religiosity and organizational commitment scale, with the scaling model being the Likert scale. The result of this study is that there is a significant influence between religiosity and organizational commitment. The coefficient of determination (R square) is 0.885 with a value (Sig.) by 0.000.